TINJAUAN HUKUM TENTANG TANGGUNG JAWAB PT. JALUR NUGRAHA EKAKURIR (JNE) CABANG KOTA SAMARINDA AKIBAT KERUSAKAN BARANG DALAM PENGANGKUTAN JASA PENGIRIMAN MENURUT UNDANG – UNDANG NOMOR 38 TAHUN 2009 TENTANG PENGIRIMAN POS - Hendra Christian Pardamean (Journal of Law ( Jurnal Ilmu Hukum ), 2016)
ABSTRACT The problems posed in this research is how the responsibility of PT. Jalur Nugraha Ekakurir ( JNE ) as a result of negligence which caused damage to or loss of goods , consumer protection in the agreement how the delivery of goods and how the settlement of disputes in the agreement which refers to the delivery of goods Act No. 38 of 2009 about post and the Act No. 8 of 1999 about consumer protection . To discuss the problems mentioned above, the juridical empirical research is a study with the approach of library research and field research at PT . Jalur Nugraha Ekakurir ( JNE ) Branch Office in Samarinda City. Results of research and discussion to explain that (JNE) is responsible for replacing losses due to damage to the document sender or goods by JNE all such losses occur when the goods are still in control JNE. Consumers can ask for compensation, restitution refers to Article 1243 BW stating that replacement costs, damages and interest due to non fulfillment of a commitment, in this case the replacement cost of damages was born as a result of default actions businesses are negligent in its duties and making consumer goods experience damage. Settlement of disputes in the agreement is done by delivery of goods: Non Litigation, settlement of consumer disputes out of court was held to reach agreement on the form and amount of compensation and / or on certain actions to ensure there is no re-occurrence of the loss suffered by consumers. Litigation, legal basis for filing a lawsuit in court contained in Article 45 paragraph (1) Act No. 8 of 1999 on Consumer Protection.  Keywords: Responsibility, Service Delivery, Failure, Damaged, Consumer Protection Act